Artifical Excitation of Ferro-Resonance for Testing Electrotechnical Equipment in Distribution Devices with Increased Voltage - Ye. V. Dmitriev; A. M. Hashimov; S. I. Hasanova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
On the basis of the developed device for protection against of ferro-resonant and high-frequency cumulative over-voltages an algorithm for obtaining a voltage imitating ferro-resonant over-voltages is proposed in the paper. This algorithm presupposes to apply a voltage to the secondary transformer side from an extraneous source is proposed.